Manajemen Rantai Pasok dan Kinerja Agroindustri Pangan Lokal Sagu di Propinsi Maluku: Suatu Pendekatan Model Persamaan Struktural - Natelda Rosaldiah Timisela; Masyhuri Masyhuri; Dwidjono Hadi Darwanto; Slamet Hartono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
The purpose of this study was to: (1) determine the mechanism of supply chain and the pattern of sago agroindustry supply chain flow, (2) analyze the relationship between the components of supply chain management (SCM) and the impact on supply chain activity improvement and agroindustry performance. Study sample of 102 sago producers were taken by simple random sampling, the study used questionnaires and in-depth interviews with respondents. The data was analyzed by qualitative and quantitative analysis. Qualitative analysis was used to describe the mechanism and pattern of sago agroindustry supply chain flow. While quantitative analysis was used to analyze the components, SCM activity improvement and agroindustry performance by using a structural equation model. The results showed that the mechanism of sago agroindustry supply chain is the creation of collaboration and coordination among supply chain actors ranging from upstream to downstream. The pattern of supply chain flow consists of raw material flow, product flow, financial flow and information flow which is run well. The results of the analysis of the structural statistics index measurement were GFI (0.901), AGFI (0.857), TLI (.994), CFI (0.995), Cmin / DF (1.022), RMSEA (0.015), the probability (0.423) and the value of χ2 (84.834). They are within the range of values expected to meet the criteria.ABSTRAKTujuan penelitian ini adalah 1) mengetahui mekanisme rantai pasok dan pola aliran rantai pasok agroindustri sagu, 2) menganalisis pengaruh komponen-komponen manajemen rantai pasok (MRP)terhadap peningkatan aktivitas rantai pasok dan kinerja agroindustri. Sampel penelitian berjumlah 102 pengrajin sagu diambil secara simple random sampling, penelitian menggunakan kuesioner dan wawancara mendalam dengan responden. Analisis data secara kualitatif dan kuantitatif. Analisis kualitatif untuk mendeskripsikan mekanisme dan pola aliran rantai pasok agroindustri sagu. Sedangkan analisis kuantitatif untuk menganalisis komponen, aktivitas rantai pasok dan kinerja agroindustri menggunakan model persamaan struktural. Hasil penelitian menunjukan bahwa mekanisme rantai pasok agroindustri sagu yang terjadi yaitu terciptanya kolaborasi dan koordinasi diantara pelaku rantai pasok mulai dari hulu sampai ke hilir. Pola aliran rantai pasok yang terdiri dari aliran bahan baku, aliran produk, aliran finansial dan aliran informasi berlangsung baik dan lancar. Hasil analisis terhadap pengukuran indeks struktural statistik seperti indeks pengukuran GFI (0,901), AGFI (0,857), TLI (0,994), CFI (0,995), CMIN/DF (1,022), RMSEA (0,015), probabilitas (0,423) dan nilai χ2 (84,834). Data tersebut berada dalam rentang nilai yang diharapkan memenuhi kriteria.